Breast cancer at the micrometre scale - Gosling, Sarah (Cranfield University, 2020)
Microcalcifications are deposits of calcium phosphate commonly found in association with some types of breast cancer. Calcifications are usually detected as bright white spots on a mammogram. Diagnosis of some breast diseases is linked to the morphology and distribution of microcalcifications, but these deposits are rarely investigated as individual entities.Multiple techniques have been used to investigate individual calcifications, including histological staining (H&E), scanning electron microscopy (SEM), elemental analysis (EDS) and x-ray diffraction (XRD). Together, these techniques allow a better understanding of the structure of the crystalline and tissue elements of breast calcifications at the micrometre scale, which may provide an insight in their formation mechanisms and possible functions. Ultimately, deciphering calcification chemistry could lead to their use as novel prognostic markers for breast disease.
Keywords: 'DSDS20 Digital Image'; 'Breast Cancer'; 'X-ray diffraction'; 'Hydroxyapatite'; 'DSDS20'; 'Cancer'; 'Cancer Diagnosis'